Earth's collision with a solar filament on 21 January 2005: Overview. Issue 10 (1st October 2013) - Kozyra, J. U.; Manchester, W. B.; Escoubet, C. P.; Lepri, S. T.; Liemohn, M. W.; Gonzalez, W. D.; Thomsen, M. W.; Tsurutani, B. T.
Abstract [1] On 21 January 2005, one of the fastest interplanetary coronal mass ejections (ICME) of solar cycle 23, containing exceptionally dense plasma directly behind the sheath, hit the magnetosphere. We show from charge‐state analysis that this material was a piece of the erupting solar filament and further, based on comparisons to the simulation of a fast CME, that the unusual location of the filament material was a consequence of three processes. As the ICME decelerated, the momentum of the dense filament material caused it to push through the flux rope toward the nose. Diverging nonradial flows in front of the filament moved magnetic flux to the sides of the ICME. At the same time, reconnection between the leading edge of the ICME and the sheath magnetic fields worked to peel away the outer layers of the flux rope creating a remnant flux rope and a trailing region of newly opened magnetic field lines. These processes combined to move the filament material into direct contact with the ICME sheath region. Within 1 h after impact and under northward interplanetary magnetic field (IMF) conditions, a cold dense plasma sheet formed within the magnetosphere from the filament material. Dense plasma sheet material continued to move through the magnetosphere for more than 6 h as the filament passed by the Earth. Densities were high enough to produce strong diamagnetic stretching of the magnetotail despite the northward IMF conditions and low levels of magnetic activity. The disruptions from the filament collision are linked to an array of unusual features throughout the magnetosphere, ionosphere, and atmosphere. These results raise questions about whether rare collisions with solar filaments may, under the right conditions, be a factor in producing even more extreme events.